Efectos de la ausencia de un sistema de control interno en la gestión del almacén de la empresa Ingepozos Cali S.A.S - Arias Osorio, Nathaly; Castaño Tasama, Jonathan (Universidad Antonio Nariño, 2021)
The company Ingepozos SAS that has been operating since 2011 in Candelaria - Valle, although for now it is not a large company is in the process of growth and is increasingly recognized in the sector as it provides agro-industrial services to large companies in the agricultural area of the Valley. Due to this growth it is necessary that all its processes are carried out efficiently.